Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Kinerja Karyawan Melalui Organizational Citizenship Behavior pada Savana Hotel & Convention Malang - Dinda Cahya Imana; Ryan Basith Fasih Khan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the variables that influence employee performance and their influence on service sector employees at Savana Hotel and Convention Malang. The type of research used is quantitative with an explanatory approach. Primary data in this study used a questionnaire which was distributed using a questionnaire sheet. The population in this study were employees of the Savana Hotel and Convention Malang and a sample of 100 respondents. Using the Partial Least Square (PLS) analysis method 4. Based on the research results, it shows that the variables of organizational culture and organizational commitment have a significant effect on employee performance at the Savana Hotel and Convention. And the organizational citizenship behavior (OCB) variable is able to mediate organizational culture and organizational commitment on employee performance for Savana Hotel and Convention employees. It can be concluded that if organizational culture improves it will support the formation of organizational commitment then these two variables will encourage high levels of organizational citizenship behavior (OCB), this is usually called employee loyalty, this will increase employee performance.